2018
DOI: 10.1371/journal.pone.0204618
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and the altered reaction to it in Fabry disease: A possible target for cardiovascular-renal remodeling?

Abstract: BackgroundFabry disease is characterized by deficient expression/activity of α-GalA with consequent lysosomal accumulation in various organs of its substrate Gb3. Despite enzyme replacement therapy, Fabry disease progresses with serious myocardial, cerebral and renal manifestations. Gb3 accumulation may induce oxidative stress (OxSt), production of inflammatory cytokines and reduction of nitric oxide, which may impact on Fabry disease’s clinical manifestations.MethodsOxSt status was characterized in 10 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Cardiac energy metabolism was also shown to be altered in FD [ 35 ]. In GLA-null cardiomyocytes, Gb3 accumulation associates with impaired autophagic flux, alteration of mitochondrial membrane potential, and increased ROS production [ 40 , 63 , 64 ]. These evidence suggest the crosstalk between loss of GAL activity and mitochondria dysfunction in cardiac cells.…”
Section: The Cardiac Phenotypementioning
confidence: 99%
“…Cardiac energy metabolism was also shown to be altered in FD [ 35 ]. In GLA-null cardiomyocytes, Gb3 accumulation associates with impaired autophagic flux, alteration of mitochondrial membrane potential, and increased ROS production [ 40 , 63 , 64 ]. These evidence suggest the crosstalk between loss of GAL activity and mitochondria dysfunction in cardiac cells.…”
Section: The Cardiac Phenotypementioning
confidence: 99%
“…We have recently provided clear evidence, using a molecular biology approach, that in Fabry patients under ERT, oxidative stress is activated in terms of the increased protein expression of p22 phox and increased level of MDA, suggesting that in Fabry patients oxidative damage affects lipid structures—contributing in the medium- to long-term to the onset of pathological processes and leading to cardiovascular-renal and cerebrovascular damage [ 34 ]. Furthermore, we have shown that the Rho kinase pathway is activated in Fabry patients, evidencing a significantly increased phosphorylation status of its target MYPT-1 and suggesting that Rho kinase activation may play an important role in the oxidative stress signaling and cardiovascular renal remodeling of Fabry patients [ 34 ]. In addition, we have also shown an altered reaction to oxidative stress in Fabry patients in terms of the reduced production of Heme Oxigenase-1 [ 34 ], induced by and protective toward oxidative stress [ 35 ].…”
Section: Oxidative Stress and Fabry Diseasementioning
confidence: 99%
“…Furthermore, we have shown that the Rho kinase pathway is activated in Fabry patients, evidencing a significantly increased phosphorylation status of its target MYPT-1 and suggesting that Rho kinase activation may play an important role in the oxidative stress signaling and cardiovascular renal remodeling of Fabry patients [ 34 ]. In addition, we have also shown an altered reaction to oxidative stress in Fabry patients in terms of the reduced production of Heme Oxigenase-1 [ 34 ], induced by and protective toward oxidative stress [ 35 ]. This dysregulation—in addition to the Rho kinase signaling and oxidative stress activation—may further contribute to the cardiovascular-renal remodeling of Fabry patients, adding further information to our understanding of the pathophysiology of Fabry disease organ damage.…”
Section: Oxidative Stress and Fabry Diseasementioning
confidence: 99%
“…Gb-3 accumulation induced reactive oxygen species (ROS) production, suppressed mitochondrial antioxidant superoxide dismutase 2 (SOD2), and enhanced AMP-activated protein kinase (AMPK) activation in vascular endothelial cells and iPS cells derived from FD patients [72,73]. The cardiomyocytes (CM) differentiated from GLA-null embryonic stem cells (ESCs) showed accelerated level apoptosis due to impairment of protein degradation and autophagic flux in the presence of Gb-3 accumulation [74]. Also, MitoSOXRed staining demonstrated an increased level of residual oxygen consumption (ROX)production in GLA-null CMs [74].…”
Section: Cardiac Energy Metabolism In Fabry Diseasementioning
confidence: 99%
“…The cardiomyocytes (CM) differentiated from GLA-null embryonic stem cells (ESCs) showed accelerated level apoptosis due to impairment of protein degradation and autophagic flux in the presence of Gb-3 accumulation [74]. Also, MitoSOXRed staining demonstrated an increased level of residual oxygen consumption (ROX)production in GLA-null CMs [74]. Therefore, dysfunctional mitochondria could be a source of ROS elevation.…”
Section: Cardiac Energy Metabolism In Fabry Diseasementioning
confidence: 99%